Predictors for individual patient antibiotic treatment effect in hospitalized community-acquired pneumonia patients. (October 2017) - Simonetti, A.F.; van Werkhoven, C.H.; Schweitzer, V.A.; Viasus, D.; Carratalà, J.; Postma, D.F.; Oosterheert, J.J.; Bonten, M.J.M.
Abstract: Objective: Our objective was to identify clinical predictors of antibiotic treatment effects in hospitalized patients with community-acquired pneumonia (CAP) who were not in the intensive care unit (ICU). Methods: Post-hoc analysis of three prospective cohorts (from the Netherlands and Spain) of adult patients with CAP admitted to a non-ICU ward having received either β-lactam monotherapy, β-lactam + macrolide, or a fluoroquinolone-based therapy as empirical antibiotic treatment. We evaluated candidate clinical predictors of treatment effects in multiple mixed-effects models by including interactions of the predictors with empirical antibiotic choice and using 30-day mortality, ICU admission and length of hospital stay as outcomes. Results: Among 8562 patients, empirical treatment was β-lactam in 4399 (51.4%), fluoroquinolone in 3373 (39.4%), and β-lactam + macrolide in 790 (9.2%). Older age (interaction OR 1.67, 95% CI 1.23–2.29, p 0.034) and current smoking (interaction OR 2.36, 95% CI 1.34–4.17, p 0.046) were associated with lower effectiveness of fluoroquinolone on 30-day mortality. Older age was also associated with lower effectiveness of β-lactam + macrolide on length of hospital stay (interaction effect ratio 1.14, 95% CI 1.06–1.22, p 0.008). Conclusions: Older age and smoking could influence the response to specific antibiotic regimens. The effect modification of age and smoking should be considered hypothesis generating to be evaluated in future trials.